2022
DOI: 10.3233/kca-220004
|View full text |Cite
|
Sign up to set email alerts
|

What We Have Learnt from CARMENA and SURTIME and What Should Be Done Differently in Future Trials on Cytoreductive Nephrectomy

Abstract: Upfront cytoreductive nephrectomy (CN) was the standard treatment for selected patients with metastatic Renal Cell Carcinoma (RCC) in the cytokine era for many years. In the recent ‘targeted therapy era’ it has been re-challenged by both the CARMENA and SURTIME trials. As first-line therapy for treatment-naive metastatic clear-cell RCC has now changed to immune checkpoint inhibitor combination therapy (ICI), and previous studies concerning CN were built in the targeted therapy era, the role and sequence of CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a post-hoc analysis of the sunitinib-alone arm, 40 patients who underwent deferred CN showed improved OS compared to those not receiving surgery, with a median 48.5 vs. 15.7 months, respectively [ 25 ]. Subgroup analyses of the intermediate risk groups in the CARMENA trial with 2 IMDC risk factors as well as 89% of the SURTIME participants indicated a favorable prognosis in the deferred CN or sunitinib alone arms compared to upfront nephrectomy (31.2 vs. 17.6 mo in the CARMENA trial and 34.2 vs. 15.0 mo in the SURTIME trial, respectively) [ 26 ]. Singla et al [ 23 ] found similar results, with patients receiving deferred CN having lower pathologic stage, grade, tumor size, and lymphovascular invasion in comparison to those undergoing upfront CN in a subgroup analysis in IO+CN patients from a national registry.…”
Section: Timing Of Surgery – Upfront or Deferred?mentioning
confidence: 99%
“…In a post-hoc analysis of the sunitinib-alone arm, 40 patients who underwent deferred CN showed improved OS compared to those not receiving surgery, with a median 48.5 vs. 15.7 months, respectively [ 25 ]. Subgroup analyses of the intermediate risk groups in the CARMENA trial with 2 IMDC risk factors as well as 89% of the SURTIME participants indicated a favorable prognosis in the deferred CN or sunitinib alone arms compared to upfront nephrectomy (31.2 vs. 17.6 mo in the CARMENA trial and 34.2 vs. 15.0 mo in the SURTIME trial, respectively) [ 26 ]. Singla et al [ 23 ] found similar results, with patients receiving deferred CN having lower pathologic stage, grade, tumor size, and lymphovascular invasion in comparison to those undergoing upfront CN in a subgroup analysis in IO+CN patients from a national registry.…”
Section: Timing Of Surgery – Upfront or Deferred?mentioning
confidence: 99%